The acute effects of cannabis on human executive function. Issue 7 (October 2018) - Oomen, Priscilla P.; van Hell, Hendrika H.; Bossong, Matthijs G.
Abstract : Cannabis remains the most frequently used illicit drug worldwide. It produces a broad range of acute effects, such as euphoria, increased heart rate and perceptual alterations. Over the last few decades, a substantial number of experiments have been conducted to provide insight into the acute effects of cannabis on cognition. Here, we systematically review studies that investigated the impact of administration of cannabis or [INCREMENT] 9 -tetrahydrocannabinol, the main psychoactive constituent of cannabis, on human executive function, in particular, on the three principal domains of inhibition, working memory and reasoning/association. Our findings suggest that cannabis use results in acute impairment of inhibition, with the strongest effects after pulmonary administration of higher doses of [INCREMENT] 9 -tetrahydrocannabinol. Results from neuroimaging studies indicate that these effects are predominantly modulated through neural processes in the inferior frontal gyrus. Working memory and reasoning/association are less clearly affected by cannabis administration, possibly because of compensational neural mechanisms to overcome the effects of cannabis intoxication on performance accuracy. Factors that may account for the variation in results are the extent to which a paradigm involves attentional processes, differences between studies in administration methods and variation in the patients' history of cannabis use. Abstract : Supplemental Digital Content is available in the text.